2015
DOI: 10.5194/acp-15-10167-2015
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium excess in the atmospheric water vapour of a Mediterranean coastal wetland: regional vs. local signatures

Abstract: Abstract. Stable isotopes of water vapour represent a powerful tool for tracing atmospheric vapour origin and mixing processes. Laser spectrometry recently allowed high timeresolution measurements, but despite an increasing number of experimental studies, there is still a need for a better understanding of the isotopic signal variability at different time scales. We present results of in situ measurements of δ 18 O and δD during 36 consecutive days in summer 2011 in atmospheric vapour of a Mediterranean coasta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 86 publications
5
52
0
Order By: Relevance
“…Diurnal water vapor isotope cycles have been widely reported and generally appear to be independent of continentality or vegetation type. Diurnal cycles of δ 18 O and d at UMBS are similar to those observed in coastal New Haven (Lee et al, ; Lee et al, ), above a wheat field (Zhang et al, ) and arid oasis cropland (Huang & Wen, ) in North China, in a coniferous forest in the Pacific Northwest (Lai & Ehleringer, ), above a Mediterranean coastal wetland (Delattre et al, ), in an evergreen forest in Northern California (Simonin et al, ), and in an isotope enabled large‐eddy simulation of the atmospheric boundary layer (Lee et al, ). Welp et al () reported on water vapor d from six sites in the United States and China, including a broadleaf deciduous forest site in Borden, Ontario, near UMBS.…”
Section: Discussionsupporting
confidence: 65%
“…Diurnal water vapor isotope cycles have been widely reported and generally appear to be independent of continentality or vegetation type. Diurnal cycles of δ 18 O and d at UMBS are similar to those observed in coastal New Haven (Lee et al, ; Lee et al, ), above a wheat field (Zhang et al, ) and arid oasis cropland (Huang & Wen, ) in North China, in a coniferous forest in the Pacific Northwest (Lai & Ehleringer, ), above a Mediterranean coastal wetland (Delattre et al, ), in an evergreen forest in Northern California (Simonin et al, ), and in an isotope enabled large‐eddy simulation of the atmospheric boundary layer (Lee et al, ). Welp et al () reported on water vapor d from six sites in the United States and China, including a broadleaf deciduous forest site in Borden, Ontario, near UMBS.…”
Section: Discussionsupporting
confidence: 65%
“…The deuterium excess values fall between 11 and 15 ‰, outside the range predicted by GNIP and characteristic of a region with enhanced evaporation (Dansgaard, 1964;Gat et al, 2003;Delattre et al, 2015). At Dumbrava (Bojar et al, 2017) and Drobeta they have similar values and variability (Fig.…”
Section: Co 2 Concentration In Cave Air and Drip Watermentioning
confidence: 56%
“…Combining online observations of d T or d ET with isotopic values of atmospheric vapour d a and land surface models informs on the interplay of water exchange between the vegetation or soils and the atmosphere. For example, ET was shown to exert a strong impact on atmospheric moisture, equalling or exceeding that of atmospheric entrainment, depending on location and season (Lai & Ehleringer, 2011;Welp et al, 2012;Delattre et al, 2015). Moreover, the impact of ET on water vapour in the planetary boundary layer, quantified in high temporal resolution (i.e.…”
Section: Vegetation Impacts On Atmospheric Moisturementioning
confidence: 99%